2007
DOI: 10.1073/pnas.0701279104
|View full text |Cite
|
Sign up to set email alerts
|

Broadly neutralizing anti-hepatitis B virus antibody reveals a complementarity determining region H3 lid-opening mechanism

Abstract: The humanized monoclonal antibody HzKR127 recognizes the preS1 domain of the human hepatitis B virus surface proteins with a broadly neutralizing activity in vivo. We present the crystal structures of HzKR127 Fab and its complex with a major epitope peptide. In the complex structure, the bound peptide forms a type IV ␤-turn followed by 310 helical turn, the looped-out conformation of which provides a structural basis for broad neutralization. Upon peptide binding, the antibody undergoes a dramatic complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…A few years ago, Chi et al reported the X-ray crystal structure of HzKR127 in complex with a major epitope peptide, which provides a structural basis for the neutralization of HBV [16]. The antibody was shown to undergo an opening of CDR to a substantial extent upon binding of the peptide antigen.…”
Section: Introductionmentioning
confidence: 97%
“…A few years ago, Chi et al reported the X-ray crystal structure of HzKR127 in complex with a major epitope peptide, which provides a structural basis for the neutralization of HBV [16]. The antibody was shown to undergo an opening of CDR to a substantial extent upon binding of the peptide antigen.…”
Section: Introductionmentioning
confidence: 97%
“…In our previous study, HzKR127 Fab displayed one of the largest conformational changes in antigen-antibody recognition [11]. The high conformational flexibility of CDR often contributes to multispecificity of antigen recognition of TCR [24][25][26] and germline antibodies [27,28,31].…”
Section: Resultsmentioning
confidence: 93%
“…4B). HzKR127 Fab bound to the epitope peptide of preS1 (36- Considering unusually high conformational flexibility observed in the crystal structure [11], the binding site of HzKR127 could change its own structure to accommodate the low-affinity site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An antiviral fusion inhibitor ''Pentafuside'' was developed against HIV following such a strategy (Chan and Kim 1998). We have been studying structural features of HBV surface antigens to gain insight into interactions between HBV and hepatocyte (Chi et al 2006(Chi et al , 2007. Preliminary CD studies showed that the preS1 exists in an unstructured state without a three-dimensional structure (Lee et al 1994;Maeng et al 2001).…”
mentioning
confidence: 99%